Lung cancer associated with cystic airspaces: current status and challenges - Wang, Linlin; Feng, Yong; Song, Shiyuan; Cao, Jiandong; Zhang, Dongxu; Yang, Hong; Ren, Yi (Frontiers in Oncology, 2025)
Lung cancer associated with cystic airspaces (LCCA) refers to primary lung cancers presenting with cystic airspaces accompanied by solid components, representing a relatively uncommon imaging and pathological phenotype. Although high-resolution imaging techniques, such as computerized tomography, are the primary diagnostic tools, early diagnosis remains challenging due to the similarity of its symptoms to other pulmonary diseases. Treatment options include surgery, chemotherapy, radiotherapy, targeted therapy, and immunotherapy. However, due to the unique nature of LCCA, treatment requires a highly individualized approach. The main challenges currently faced include improving diagnostic accuracy, determining the optimal treatment strategies, and advancing the understanding of its underlying biological characteristics. Future research will focus on optimizing diagnostic techniques, developing targeted therapies for specific molecular markers, exploring the application of immunotherapies, and promoting multidisciplinary collaboration. With continuous advancements in technology and personalized treatment strategies, significant improvements in the diagnosis and treatment of LCCA are anticipated. This review summarizes the epidemiology, imaging features, pathological characteristics, pathogenesis, treatment strategies, and challenges of LCCA, and offers perspectives on future research directions.